DAMPAK KADMIUM DAN MERKURI TERHADAP METABOLISME KARBOHIDRAT: KAJIAN IN SILICO PADA ENZIM GLIKOGEN SINTASE DAN FOSFOFRUKTOKINASE - Azka Lahdimawan; Siti Arika Bulan; Eko Suhartono; Bambang Setiawan (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Cadmium (Cd) and Mercury (Hg) is a heavy metal with high cytotoxicity, implicated as causes of chronic inflammation, oxidative stress, obesity, hyperglycemia, and even diabetes. The long-term exposure of Cd and Hg can affect enzymes involved in carbohydrate metabolism, on the process of glycolysis and glycogenesis. by changing the structure and enzymatic activity of proteins which can cause toxic effects on enzymes involved therein including glycogen synthase (GS), which can cause glycogen content depletion and has potential to limit the glycolysis process in liver and muscles by decreasing the phosphofructokinase (PFK) enzyme activity. There are not many studies that explain the interactions between Cd and Hg on GS and PFK enzymes. For this reason, this research was carried out using in silico. The structure of the enzymes was obtained from the RCSB Protein Data Bank (http://www.rcsb.org) with the following code, GS (PDB ID: 1RZV) and PFK (PDB ID: 4WLO). The interactions between Cd and Hg with these enzymes were used by MIB: Metal Ion-Binding site prediction and docking server (http://bioinfo.cmu.edu.tw/MIB/). The interactions between Cd and amino acids of targeted protein were visualized on UCSF Chimera 1.14. The results showed that Hg interacted with amino acid residues at the active site of the glycogen synthase enzyme at the end of the C-terminal domain, namely at 3 cysteine ??residues Cys 295, cys 366, and cys 390. Meanwhile, Cd and Hg did not interact with amino acid residues. on the active site of the phosphofructokinase enzyme, but interacts with the protein structure of the enzyme.